MO048: Genome-wide studies reveal factors associated with circulating uromodulin and its relations with complex diseases. (3rd May 2022) - LI, Yong; Cheng, Yurong; Consolato, Francesco; Schiano, Guglielmo; Chong, Michael; Pietzner, Maik; Quynh Nguyen, Ngoc; Scherer, Nora; Biggs, Mary; Kleber, Marcus E; Haug, Stefan; Göçmen, Burulça; et al.
Abstract: BACKGROUND AND AIMS: UMOD is a major risk gene for monogenic and complex forms of kidney disease. The encoded kidney-specific protein uromodulin is the most abundant protein in urine and related to chronic kidney disease, hypertension and pathogen defense. Through basolateral release from kidney epithelial cells, uromodulin also reaches the blood, where its function is largely unknown. To gain insights into potential systemic roles, we performed genome-wide screens of circulating uromodulin in seven cohorts using two complementary assays. METHOD: Separate genome-wide association study meta-analyses for circulating uromodulin were conducted for the antibody-based assay (five cohorts, N = 13 985) and the aptamer-based SOMAscan assay (two cohorts, N = 18 070). Genome-wide significant loci were placed into their functional genomic context using RNA-seq, ATAC-seq and Hi-C data generated from primary human kidney tissue. An array of downstream genetic analyses was then performed for significant loci, including fine-mapping, colocalization analyses and gene-by-gene interaction analyses. The B4GALNT2 p.Cys466Arg allele was expressed in MDCK cells and studied by immunofluorescence and Western blotting analyses. RESULTS: We detected and replicated 13 genome-wide significant loci (P <5e−8; 12 novel). At the UMOD locus, functional genomics data of primary human kidney tissue highlighted an upstream regulatory variant with differential accessibility and UMOD transcription in uromodulin-synthesizing kidney cells. Shared association patterns with complex traits, including chronic kidney disease and blood pressure, placed the PRKAG2 locus in the same context as UMOD . Experimental validation of another locus, B4GALNT2, showed that the detected p.Cys466Arg variant of the encoded N-acetylgalactosaminyltransferase has a loss-of-function effect leading to higher serum uromodulin levels. Lastly, our results point to enzymes writing glycan marks present on uromodulin and to their receptors in the circulation. CONCLUSION: This study provides human genetic evidence of new pathway members of uromodulin and delivers novel insights into its determinants and systemic role in the circulation.